Special Training According to Power Law and Its Effect on Some Kinetical Indicators and Achievement in 100m Sprint Under 20 Years Old - Bilal Ali Ahmed (College of Physical Education and Sport Sciences, 2020)
100m sprints is characterized by many technical artistic phases starting from the launch to acceleration and maintaining a speed that requires a great level of legs' power to change speed positively. All these phases require special training thus the researcher aimed at designing special training according to power law to specify training intensity using distances and times. The importance of the research lies in designing training according to power law as well as identifying the effect of this training on the level of 100m sprint achievement. Many variables were measured including pushing time during lunch; performance power average during sprinting using dynafoot for measuring legs' power and 100m performance time was also measured. The training was applied on 10 sprinters from Athletic clubs in Baghdad that consisted of (24) training sessions during the preparation phase. The researcher concluded a great development in the level of power during sprinting as well as an increase in the level of power push during lunch in 100m sprinter and development in 100m sprint achievement.